Persepsi Orang Tua dan Tenaga Pendidik di Desa Pucangadi Terhadap Tayangan Edukatif Sibobo di TVRI Jawa Tengah - Joko Warsito; Fitria Nur ‘Aini (Kajian Administrasi Publik dan ilmu Komunikasi, 2025)
This study examines the perceptions of the Pucangadi Village community towards the educational children's program "SiBobo" broadcast by TVRI Central Java. This research uses a descriptive qualitative approach, with data collection techniques through in-depth interviews with fifteen informants selected purposively. Informants consisted of parents, teachers, and local residents who have views regarding the program. The purpose of this study was to explore the extent to which the program "SiBobo" is accepted and has a positive impact on the development of children in the community. The results showed that the program "SiBobo" is considered an entertaining and educational learning medium by the majority of informants. This program successfully conveys moral and social messages relevant to children's lives, such as the values ​​of togetherness, social awareness, and the importance of protecting the environment. This program is also considered able to attract children's attention in a fun way, making them interested in learning while playing. In addition, the content presented in this program can increase children's knowledge about local culture and wisdom, which is expected to increase their love for Indonesian culture. However, despite "SiBobo"'s high educational value, the presence of gadgets and children's preference for digital content, such as YouTube videos and game apps, often divert their attention from public television. Children are more interested in shows they can access anytime through their devices. This suggests that while television shows like "SiBobo" still play a significant role, competition from digital media presents a significant challenge. This study emphasizes the importance of revitalizing children's programming based on local values ​​and the need for more adaptive communication strategies to optimally convey educational messages.